Estimation of ‘Stature’ from Long Bones of the Lower Limb-A Cadaver based Study (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and objectives: Stature of a person is an important parameter of personal identification. Inthis study stature ( body total length) was estimated from the measurement of length of femur and tibiabelonging to unclaimed cadavers. Methodology: a total number of 51 unidentified dead bodies (42 maleand 9 female) in age group of 18-80 years were studied. Length of the body of the study subject in lyingposition on autopsy table, length of the fresh and dry bones of femur and tibia were measured. Regressionformulae and Multiplication factors were derived for both sexes for fresh and dry bones of femur and Tibiafor estimation of stature. Results: Among males; Wet femur shows highest correlation with the stature,while wet tibia shows least correlation, though both show significant correlation for the estimation of stature(P< 0.0001). Among females ; Dry femur, and combined dry femur and tibia shows highest correlationwith the stature, while wet tibia shows least correlation, though both shows significant correlation for theestimation of stature (P< 0.0001). Interpretation and Conclusion: This study will be useful to the forensicmedical experts when only the lower limb is available for forensic investigation in estimating stature andin anthropological research projects. Regression formulae are dependable than multiplication factor forestimation of stature [52].
Keywords: forensic, regression formula, Stature estimation, lower limb bones, cadaver based study.